Statistical Analysis for Hull Stress Monitoring Network Signal with Nested Array. (11th October 2015) - Wang, Wei; Qin, Shan
The hull stress monitoring system is to measure and display the ship motions and real-time stresses by strain gauge and accelerometer sensor networks. The statistical parameters such as standard deviation of measurements through hull stress sensor network are important for analysis of hull structure status. Due to the large amount of measurement data, it is difficult to acquire the standard deviation directly. Nested array is a sparse sampling algorithm which can keep the statistical property of the original data. This paper presents an algorithm for standard deviation computed of hull stress data based on nested array. From the experimental results, it can be seen that the provided algorithm can achieve higher accurate distribution of standard deviation with much less samples. This proves that the nested array sampling could be used in statistical computing for hull stress data.